The Effect of the Pesantren Educational Environment on the Cardiovascular Fitness Outcomes of Seventh-Grade Students at MTs Manba’ul Hikam - Aprillia Savita Della; Heryanto Nur Muhammad (FKIP - Universitas Riau, 2026)
The pesantren environment has distinctive characteristics, particularly a dense schedule of academic, religious, and boarding activities, which may influence students’ cardiovascular fitness. This study aimed to analyze the effect of the pesantren context on the cardiovascular fitness of seventh-grade students at MTs Manbaul Hikam. A descriptive quantitative approach with mixed methods was employed. Primary data were obtained through cardiovascular fitness measurements using the Progressive Aerobic Cardiovascular Endurance Run (PACER) Test, while supporting data were collected through semi-structured interviews. The research involved 174 seventh-grade students from five classes. Interviews were conducted with a Physical Education teacher, a pesantren supervisor, and three students to explore daily activity patterns. The results showed that students’ overall cardiovascular fitness was in the low category. Although Physical Education lessons and sports extracurricular activities were provided, students’ participation levels and physical activity intensity were uneven. Interview findings revealed that the dense daily schedule and limited rest time were significant factors affecting students’ fitness. In conclusion, the pesantren context influences students’ cardiovascular fitness through the regulation of daily activities and lifestyle patterns, indicating the need for better balance between academic, religious, and physical activities.